ANALISIS POTENSI EKONOMI DAERAH KABUPATEN BONE BOLANGO - Ramlah Alkatiri; Haryono Panigoro (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2021)
One indicator to determine the ability of an area to grow and develop rapidly is by analyzing the economic potential of the area. This study aims to determine how the economic potential of Bone Bolango Regency. This study uses a quantitative approach using a secondary database, namely time series data (time series) of Gross Regional Domestic Product for the last 5 years (2015-2019).The results showed that the economic potential of Bone Bolango Regency is classified as having potential Basic sectors consisting of 10 sectors or business fields respectively are: 1) Mining and Quarrying, 2) Manufacturing Industry, 3) Construction, 4) Wholesale and Retail Trade, 5 ) Real estate, 6) corporate services, 7) government administration, 8) education services, 9) health services, and 10) services. The non-base sector of Bone Bolango Regency consists of 7 sectors or business fields respectively; 1) Agriculture, 2) Procurement of Electricity and Gas, 3) Transportation and Warehousing, 4) Provision of Water, Garbage, Waste, 5) Provision of Accommodation and Food and Drink, 6) Information and Communication, and 7) Financial Services and Insurance. The economic growth that occurs is influenced by the dominance of the basic sector owned by Bone Bolango Regency in the formation of GRDP in the last 5 years (2015-2019).